RANCANGAN HIDROLlKA IRIGASI TETES UNTUK TANAMAN SEMANGKA DI LAHAN KELOMPOK TANI SEROPAN MAKMUR, KABUPATEN GUNUNG KIDUL, D.I. YOGYAKARTA - Prastowo Prastowo; S. Hardjoamidjojo; Y. K. Awang (PERTETA, 2007)
ABSTRACT Hydraulic design of trickle irrigation sub unit is very important to achieve high irrigation uniformity and efficiency of its schemes. The sub unit is a pipeline in a trickle irrigation block which is consists of a manifold line, some laterals and emitters. The hydraulic criteria has been used in the design of trickle irrigation scheme for water melon (Citrullus vulgaris L.) at an existing pipeline system of surface irrigation scheme in Seropan Area, Yogyakarta. The hydraulic criteria includes pipeline hydraulics of lateral and manifold, system capacity, and total dynamic head. The number and size of sub unit has been designed, and the head losses (hf) at lateral and manifold were ≤ 11% and ≤ 9% of emitter operating pressure (Ha) respectivel. Theoritically, variation of emitter discharge will vary at 1.16-1.61%. Diterima: 2 Januari 2007; Disetujui: 30 Januari 2007